Experimental Infection of Reindeer with Jamestown Canyon Virus - Kayla J. Buhler; John Blake; Heather Fenton; Isaac H. Solomon; Emily Jenkins (Emerging Infectious Diseases)
Seroprevalence of Jamestown Canyon virus in free-ranging caribou in North America is high. We demonstrate serum antibodies and RNA of the virus in blood and tissues of experimentally exposed reindeer with no clinical illness and minimal histopathologic changes. Caribou and reindeer may play a role in emergence and dissemination of vectorborne zoonoses in Arctic regions.